The DNA polymerase gene from the methanogenic archaeon Methanococcus voltae. - Konisky, J (1994)
Previous studies have identified intervening sequences that encode homing endonucleases within the genes encoding several archaeal DNA polymerases. We report the sequence of the gene encoding the DNA polymerase of Methanococcus voltae and describe evidence that it lacks analogous intervening sequences.